The Influence of Early Motivation to Become a Customer on the Satisfaction of Sharia Bank Depositors in DKI Jakarta - Supriyono (Maaliyah: Journal of Islamic Economic Law and Islamic Finance, 2025)
The purpose of the research is to find out the difference in customer satisfaction levels of saving customers reviewed from the beginning of bank account opening, termed 'Voluntary Customer' or 'Forced Customer'. This research is a field study with the population of Saving Customers in Sharia Bank operating in the Special Region of Jakarta. The number of samples that met the requirements was 394 consist of 'Voluntary Customer' as many as 247 respondents and 'Forced Customer' as many as 147 respondents. The questionnaire was set in five points Likert scales. Validity Test using Product Moment Correlation and Reliability Test using Chronbah Alpha. The results of the study are as follows: Customer satisfaction of Sharia Bank is still very low. There is a significant difference between the satisfaction of 'Voluntary Customer' and 'Forced Customer'. There is a significant difference between the satisfaction of 'Voluntary Customers who know the contract' and 'Forced Customers who do not know the contract'. There is no significant difference between the satisfaction of 'Voluntary Customer who knows the contract' and 'Voluntary Customer who does not know the contract'. There is no significant difference between the satisfaction of 'Forced Customer who knows the contract' and 'Forced Customer who does not know the contract'. There is no significant difference between the satisfaction of 'Voluntary Customers who do not know the contract' and the 'Forced Customer who knows the contract'.